Elicitor-driven enhancement of phenolic compounds in geranium callus cultures: phytochemical profiling via LC-MS/MS and biological activities - Elbouzidi, Amine; Taibi, Mohamed; Baraich, Abdellah; Haddou, Mounir; Mothana, Ramzi A.; Alsufyani, Sami A.; Darwish, Hany W.; Molinié, Roland; Fontaine, Jean-Xavier; Fliniaux, Ophélie; Mesnard, François; Addi, Mohamed (Frontiers in Chemistry, 2025)
This research explores the effects of chitosan (CHT) and salicylic acid (SA) as elicitors on the production of phenolic and flavonoid compounds in Pelargonium graveolens Hort. Callus cultures on solid media, aiming to enhance antioxidant, anti-tyrosinase, and anti-elastase properties. Calli were treated with various concentrations of CHT (25, 50, 75, and 100 mg/mL) and SA (25, 50, 75, and 100 µM), and their phytochemical profiles were examined through LC-MS/MS analysis. The findings indicated that salicylic acid (SA) and chitosan (CHT) notably enhanced the levels of total phenolic content (TPC) and total flavonoid content (TFC). The greatest increase in TPC was seen in cultures treated with 25 µM of salicylic acid (SA2), recording 336.80 ± 8.35 mg/100 g dry weight (DW), and in cultures treated with 100 mg/mL of chitosan (CHT5), which showed 325.74 ± 7.81 mg/100 g DW. Among individual phenolics, kaempferol showed a remarkable increase under SA2 (192.82 ± 17.99 mg/100 g DW) compared to the control (103.68 ± 5.00 mg/100 g DW), and CHT5 treatment (119.68 ± 12.01 mg/100 g DW). Additionally, rutin accumulation peaked at 30.64 ± 3.00 mg/100 g DW under SA2 treatment. Antioxidant activities, measured by DPPH and TAC assays, were also enhanced, with SA2 and CHT5 treatments showing significant improvement over the control. The SA2-elicited cultures exhibited superior anti-tyrosinase and anti-elastase activities, with IC50 values of 51.43 ± 1.31 μg/mL, 35.42 ± 4.42 μg/mL, and 31.84 ± 0.60 μg/mL, respectively. These findings suggest that elicitors effectively boost the bioactive compound production in P. graveolens calli, and subsequently the biological activity, highlighting their potential in developing natural skincare products with antioxidant and anti-aging benefits.